Interdisciplinary Comparison of Scientific Impact of Publications Using the Citation-Ratio - Arthur R. Bos; Sandrine Nitza (Data Science Journal, 2019)
The commonly used indexes for evaluating the scientific impact of publications and individual researchers do not allow accurate comparison between disciplines with varying citation frequencies. The Citation-Ratio (CR) was developed to measure impact of an individual publication and allow field-normalised comparison. The CR equals the total number of citations of a publication divided by the median of citations of its references and was tested for the top 5% of the most-cited publications of 13 selected disciplines in sciences, social sciences and humanities. Each publication had a CR = 0 until it was firstly cited. At CR = 1 the number of citations equalled the median of citations of the references. CRs of the most-cited publications mostly ranged between 1 and 10 and were not significantly different across the selected disciplines. In contrast, the total number of citations of the same publications were significantly different across disciplines. One of the advantages of the CR is that it can be calculated for any publication as long as it has references (e.g. books, book chapters, reports, and symposium contributions).